Sulfidation forwarding high-strength Anammox process using nitrate as electron acceptor via thiosulfate-driven nitrate denitratation. (January 2022) - Lin, Wenmin; Feng, Jiyu; Hu, Keqiang; Qu, Bingyu; Song, Song; He, Kuang; Liu, Chang; Chen, Yuancai; Hu, Yongyou
Graphical abstract: Highlights: High TN removal (83.66%) was achieved at the NLR of 2.6 kg-N/(m 3 ·d) in TDSA. Sulfate production was greatly reduced in TDSA system. Unique S 0 @ Anammox granules could tolerate high FA and DO. The contributions of various nitrogen removal pathways were investigated. Nitrogen and sulfur conversion mechanism in TDSA system was proposed. Abstract: A single up-flow thiosulfate-driven nitrate denitratation coupled with the sulfurized Anammox (TDSA) with the core–shell structure (S 0 @ Anammox granules) provided a chemical/energy-saving way for the removal of high-content ammonium with nitrate as electron acceptor. Approximately 83.66% total nitrogen removal efficiency (TNRE) could be achieved by the sulfurized Anammox encrusted by S 0 /Sn 2− at a high loading rate (2.6 kg-N/(m 3 ·d)) via resisting high concentration of free ammonia (FA) (22.35 mg/L), mainly through S2 O3 2−, S 0 /Sn 2− -driven partial denitrification-Anammox (PDN-Anammox) process. Moreover, S 0 /Sn 2− -PDN-Anammox was largely restricted when intermittently aerated, but still resulting in 74.47% TNRE due to the partial nitrification-Anammox (PN-Anammox). The sequencing analysis revealed that Anammox bacterium ( Candidatus_Kuenenia ) and sulfur-oxidizing bacterium ( Thiobacillus ) coexisted, in which Anammox process occurred mainly via NO instead of NH2 OH. This study provided a new perspective for high concentration nitrogen wastewater removal in engineering applications.